Pemanfaatan Seni Drama sebagai Media Pendidikan Karakter bagi Siswa di SMP Negeri 4 Desa Telangkah, Katingan Hilir - Mayangsari, Marrisa Aulia Mayangsari; Andi Arie Astuti; Yuliati Eka Asi; Muhammad Ahsin Maulana; Muh Andis Hidayullah (Universitas Negeri Surabaya, 2025)
Currently, character education has become a fundamental aspect in shaping the personality of the nation's next generation. Character education has become part of the national education system to ensure that future generations possess not only academic intelligence but also sound moral foundations. Character education can be instilled through learning media in schools. Drama, in this case, has excellent potential to become a fun and engaging character education medium for students. Drama trains students to develop empathy, responsibility, discipline, teamwork, selfconfidence, and creativity. This research focuses on the use of drama as a medium for character education at SMPN 4 Telangkah Village, Katingan Hilir. In general, the purpose of this study is to explore and analyze the use of drama in shaping student character at SMPN 4 Telangkah Village. The research method used is a qualitative approach with a case study design. The expected outputs of this research are in-depth findings regarding the practice of utilizing drama in the context of character education, as well as a scientific article published in an accredited national journal. The description of the TKT for this research is at level 3, meaning the research design and methodology are comprehensive.